Perceptions and feelings of the family member/caregiver expressed before the patient on home care - Fogaça, Naianny Jonas (2015)
Objectives: to analyze the perceptions and feelings expressed by relatives regarding the patient undergoing home care. Method: this is a descriptive and qualitative study, with data collection carried out through semi-structured interviews at home, developed with fourteen family members of patients assisted by a home care company. Data were organized by content analysis technique. Results: perceptions and feelings expressed were: insecurity, fear, anxiety, worry, feelings of deprivation of liberty and at the same time, gratitude for the care, comfort, safety and proximity to care control, preferring the admitted patients at home and rated the care as satisfactory. Conclusion: home care should be seen as an innovative humanized care modality that aims to reverse the logic of work of health professionals, which is not limited to meet the clinical needs of patients, but also provide necessary support to the families involved.